Conducting and dielectric properties of Na3Fe2(PO4)3 and Na2FePO4F - Nogai, A; Salikhodzha, Zh. M.; Nogai, A. S.; Uskenbaev, D. E. (Eurasian Journal of Physics and Functional Materials, 2026)
In this research, the structure parameters, conducting and dielectric properties of Na3Fe2(PO4)3 and Na2FePO4F polycrystals were studied obtained by solid-phase synthesis. The phase transition temperatures, conducting and dielectric parameters of Na3Fe2(PO4)3 and Na2FePO4F polycrystals were refined. A comparative evaluation of the conductive properties of Na3Fe2(PO4)3 and Na2FePO4F polycrystals is given in this article. The prospects of using of Na3Fe2(PO4)3 and Na2FePO4F are justified as electrode materials in sodium ion batteries.Recommended CitationNogai, A. A.; Salikhodzha, Zh. M.; Nogai, A. S.; and Uskenbaev, D. E. (2021) "Conducting and dielectric properties of Na3Fe2(PO4)3 and Na2FePO4F," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 3, Article 7.DOI: https://doi.org/10.32523/ejpfm.2021050307